O KOBIECYCH OBRAZACH W PROZIE MICHAIŁA ARCYBASZEWA - Witczak, Patryk (Acta Neophilologica, 2018)
This article focuses on the works by Mikhail Artsybashev, presenting a formation of a new relationship between men and women. Artsybashev depicts women’s aspirations to free themselves from masculinised and patriarchal society as well as their desire to become more independent. Artsybashev’s main female characters try to move beyond traditional roles of wives and mothers. Their rebellion against social norms and prohibitions takes various forms.